2005
DOI: 10.1002/pmic.200500019
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of enriched microsomal fractions from GS-NS0 murine myeloma cells with varying secreted recombinant monoclonal antibody productivities

Abstract: The folding, transport and modification of recombinant proteins in the constitutive secretory pathway of eukaryotic cell expression systems are reported to be a bottleneck in their production. We have utilised a proteomic approach to investigate the processes catalysed by proteins constituting the secretory pathway to further our understanding of those processes involved in high-level antibody secretion. We used GS-NS0 cell populations differing in qmAb to prepare enriched microsome fractions from each cell po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…This may explain some of the effects of cold shock on productivity as PDI functions as endoplasmic reticulum chaperone through participating in the folding of proteins containing disulfide bonds, PDI has also been linked to increased secretion of heterologous proteins (Robinson et al 1994;Ostermeier et al 1996;Shusta et al 1998). PDI levels were almost 2-fold higher in NS0 cells associated with high specific productivity of MAb (Smales et al 2004;Alete et al 2005). The effects of PDI on productivity may be cell lineand product-specific, but as overexpression of PDI in CHO was also shown to decrease the secretion of a disulfide-rich tumour-necrosis-factor-receptor (TNFR):Fc fusion protein (Davis et al 2000), it is possible that effects of PDI on productivity may be dependent on other factors such as BiP or ENPL (Smales et al 2004).…”
Section: The Use Of Cell Cycle Arrest To Increase Recombinant Proteinmentioning
confidence: 99%
“…This may explain some of the effects of cold shock on productivity as PDI functions as endoplasmic reticulum chaperone through participating in the folding of proteins containing disulfide bonds, PDI has also been linked to increased secretion of heterologous proteins (Robinson et al 1994;Ostermeier et al 1996;Shusta et al 1998). PDI levels were almost 2-fold higher in NS0 cells associated with high specific productivity of MAb (Smales et al 2004;Alete et al 2005). The effects of PDI on productivity may be cell lineand product-specific, but as overexpression of PDI in CHO was also shown to decrease the secretion of a disulfide-rich tumour-necrosis-factor-receptor (TNFR):Fc fusion protein (Davis et al 2000), it is possible that effects of PDI on productivity may be dependent on other factors such as BiP or ENPL (Smales et al 2004).…”
Section: The Use Of Cell Cycle Arrest To Increase Recombinant Proteinmentioning
confidence: 99%
“…HSP60 and HSC7 are both thought to have antiapoptotic functions (Kirchhoff et al 2002;Mosser et al 2000). In a related study (Alete et al 2005), the microsomal component was isolated from the same set of NS0 cells and proteomic analyses was performed, and again PDI and BiP were found to be increased with increased levels of Mab productivity. Other proteins altered were from diverse functional groups such as cellular metabolism, cytoskeletal organisation, protein turnover and mAb folding/assembly.…”
Section: High Productivitymentioning
confidence: 98%
“…Further, intracellular aggregation (Hasemann and Capra 1990;Hsu and Betenbaugh 1997;Hsu et al 1996;Hsu et al 1994;Schr枚der et al 2002), association of heterologous proteins with the molecular chaperone BiP/GRP78 (Dorner et al 1987;Hurtley et al 1989;Jarvis and Summers 1989;Kaufman et al 1988;Machamer et al 1990;Suzuki et al 1991), and dilation of the ER (Dorner et al 1989;Gennaro et al 1991) have been reported. BiP induction, a hallmark of ER stress and UPR activation, has been reported for many expression systems (Alete et al 2005;Downham et al 1996;Jones et al 2005;Miura et al 2001;Smales et al 2004). Further, even in secretory cell types such as plasma cells activation of the UPR has been observed (van Anken et al 2003;Zhang et al 2005).…”
Section: Introductionmentioning
confidence: 93%
“…Induction of BiP in several expression systems (Alete et al 2005;Dorner et al 1989;Downham et al 1996;Jones et al 2005;Miura et al 2001;Smales et al 2004;Watowich et al 1991), of NF-jB in human IL-6 expressing CHO cells (Teruya et al 2005), and of genes involved in the ER stress response including BiP, GRP94, calnexin, and HERP in human bone morphogenic protein 2 expressing CHO DUKX cells (Doolan et al 2008) demonstrates that the UPR is activated in many heterologous expression systems. Cooperativity of molecular chaperones and foldases may necessitate increasing expression of several chaperones simultaneously to reproducibly increase productivities.…”
Section: Engineering Of the Uprmentioning
confidence: 99%